Efficiency assessment of Costa Rica’s counties: A non-parametric analysis of the county competitiveness index - Araya Solano, Manuel (2019)
This study employs a Data Envelopment Analysis (DEA) model with a single constant input to scrutinize the competitive efficiency of Costa Rican counties for the year 2016. By using the seven dimensions (pillars) of the County Competitiveness Index (ICC) as outputs of the proposed non-parametric production function, the efficiency results indicate that, on average, Costa Rican counties can improve their competitive efficiency 56.84%. The findings suggest that the configuration of competitive pillars has significant implications for efficiency assessments. For more developed regions with urban agglomerations, competitive pillars related to infrastructure, employment, quality of life and innovation are relevant policy priorities shaping competitive efficiency; while employment and quality of life indicators are the main pillars explaining the competitive efficiency in less developed regions. The County Competitiveness Index is a valuable instrument to monitor counties’ competitive performance, and the proposed analytical approach ‒i.e., DEA model‒ may offer useful information to policy observers on what strategic actions can help to optimize resource allocation policies and, subsequently, county competitiveness.